Family systems approaches in pediatric obesity management: a scoping review - Natasha Wills-Ibarra; Keryn Chemtob; Heather Hart; Francesca Frati; Keeley J Pratt; Geoff DC Ball; Andraea Van Hulst (BMC, 2024)
Abstract Family-based obesity management interventions targeting child, adolescent and parental lifestyle behaviour modifications have shown promising results. Further intervening on the family system may lead to greater improvements in obesity management outcomes due to the broader focus on family patterns and dynamics that shape behaviours and health. This review aimed to summarize the scope of pediatric obesity management interventions informed by family systems theory (FST). Medline, Embase, CINAHL and PsycInfo were searched for articles where FST was used to inform pediatric obesity management interventions published from January 1980 to October 2023. After removal of duplicates, 6053 records were screened to determine eligibility. Data were extracted from 50 articles which met inclusion criteria; these described 27 unique FST-informed interventions. Most interventions targeted adolescents (44%), were delivered in outpatient hospital settings (37%), and were delivered in person (81%) using group session modalities (44%). Professionals most often involved were dieticians and nutritionists (48%). We identified 11 FST-related concepts that guided intervention components, including parenting skills, family communication, and social/family support. Among included studies, 33 reported intervention effects on at least one outcome, including body mass index (BMI) (n = 24), lifestyle behaviours (physical activity, diet, and sedentary behaviours) (n = 18), mental health (n = 12), FST-related outcomes (n = 10), and other outcomes (e.g., adiposity, cardiometabolic health) (n = 18). BMI generally improved following interventions, however studies relied on a variety of comparison groups to evaluate intervention effects. This scoping review synthesises the characteristics and breadth of existing FST-informed pediatric obesity management interventions and provides considerations for future practice and research.